2018
DOI: 10.1002/chem.201805420
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the seco‐Limonoid BCD Ring System Identifies a Hsp90 Chaperon Machinery (p23) Inhibitor

Abstract: D‐Ring‐seco‐limonoids (tetranortriterpenoids), such as gedunin and xylogranin B display anti‐cancer activity, acting via inhibition of Hsp90 and/or associated chaperon machinery (e.g., p23). Despite this, these natural products have received relatively little attention, both in terms of an enabling synthetic approach (which would allow access to derivatives), and as a consequence their structure–activity relationship (SAR). Disclosed herein is a generally applicable synthetic route to the BCD ring system of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…AIT would bind to the p23 partner of Hsp90, thereby also destabilizing certain Hsp90 client proteins, in a manner similar to the pentacyclic triterpenoid gedunin (Figure 4) which is known to bind to p23, thus blocking its cellular interaction with Hsp90, causing apoptotic cell death (Patwardhan et al, 2013). Certain gedunin analogs also inhibit p23 (Pinkerton et al, 2019). A similar situation has been reported with docosahexaenoic acid (DHA), which attenuated the Hsp90‐p23 complex leading to inhibition of two major Hsp90 client proteins: epidermal growth factor receptor 2 (ErbB2) and hypoxia‐inducible factor 1α (HIF‐1α), contributing to the anticancer activity observed in a A549 xenograft model in mice supplemented with dietary DHA (Mouradian et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…AIT would bind to the p23 partner of Hsp90, thereby also destabilizing certain Hsp90 client proteins, in a manner similar to the pentacyclic triterpenoid gedunin (Figure 4) which is known to bind to p23, thus blocking its cellular interaction with Hsp90, causing apoptotic cell death (Patwardhan et al, 2013). Certain gedunin analogs also inhibit p23 (Pinkerton et al, 2019). A similar situation has been reported with docosahexaenoic acid (DHA), which attenuated the Hsp90‐p23 complex leading to inhibition of two major Hsp90 client proteins: epidermal growth factor receptor 2 (ErbB2) and hypoxia‐inducible factor 1α (HIF‐1α), contributing to the anticancer activity observed in a A549 xenograft model in mice supplemented with dietary DHA (Mouradian et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Later, it was shown that various α-diazo-γ-butyrolactones can be synthesized in direct diazo transfer conditions at low temperatures. However, this method did not gain popularity because of the formation of large numbers of triazine and azide side-products [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ]. Much better results were achieved using detrifluoroacetylating diazo transfer, which to-date is the most widely accepted method of synthesizing α-diazo lactones, including six- and seven-membered ones ( Scheme 73 ) [ 5 , 96 , 109 , 110 ].…”
Section: α-Diazo Lactonesmentioning
confidence: 99%
“…In contrast to normal cells, heat shock protein 90 (HSP90) is continuously activated in cancer cells (15) and highly expressed in hematological malignancies, especially in acute leukemia (16). HSP90 and the co-chaperone p23 bind to human telomerase reverse transcriptase (hTERT) to activate telomerase during tumorigenesis (17,18). HSP90 expression is higher in patients with higher-risk MDS compared with patients with lower-risk MDS, and is therefore positively correlated with the risk of MDS conversion to acute leukemia and poor prognosis (19,20).…”
Section: Combination Of Hde and Biib021 Efficiently Inhibits Cell Promentioning
confidence: 99%